2009
DOI: 10.1002/pssc.200982076
|View full text |Cite
|
Sign up to set email alerts
|

Progress of the EPOS project: Gamma‐induced Positron Spectroscopy (GiPS)

Abstract: A long sought after target in materials research has been the synthesis of high quality, optically transparent, electrically conductive thin films that simultaneously provide large surface area and nanocrystalline mesoporosity. , Geoff Ozin and co‐workers report a dye‐anchored transparent, well‐ordered mesoporous antimony‐doped tin oxide film that functions as the working electrode in an electrochemiluminescent cell, suggesting opportunities for use in a range of optoelectronic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Henceforth, it is implied that positron trapping or annihilation at dislocation means annihilation at vacancies associated with dislocations. Present lifetime value is in consistent with reported experimental value of 158 ps for deformed Fe 32 . This lifetime remains constant till 523 K and starts decreasing sharply beyond 673 K. The decrease in lifetime between 523 and 823 K can be understood as annealing of dislocations along with associated vacancies.…”
Section: Resultssupporting
confidence: 92%
“…Henceforth, it is implied that positron trapping or annihilation at dislocation means annihilation at vacancies associated with dislocations. Present lifetime value is in consistent with reported experimental value of 158 ps for deformed Fe 32 . This lifetime remains constant till 523 K and starts decreasing sharply beyond 673 K. The decrease in lifetime between 523 and 823 K can be understood as annealing of dislocations along with associated vacancies.…”
Section: Resultssupporting
confidence: 92%
“…(iii) It was demonstrated that bremsstrahlung can be used to produce positrons directly in the sample [74]. Hence the master clock of the linac, which produces intense bursts of γ radiation, can serve to trigger the time measurement [75].…”
Section: Pulsed Beamsmentioning
confidence: 99%
“…Such a measurement is difficult using a slow (∼keV) positron beam. In recent years, PAS for bulk materials via Gamma-induced Positron Spectroscopy (GiPS) has been developed [5][6][7][8][9][10][11][12][13][14]. In GiPS, a high energy photon is implanted into the sample and positron generation and annihilation occurs inside the sample directly.…”
Section: Introductionmentioning
confidence: 99%